The Role of Local Communities in Implementing Soil and Water Conservation Practices for Sustainable Food Production Enhancement in the Salawati District, Sorong Regency - Fajeriana, Nurul; Ali, Akhmad (Politeknik Negeri Lampung., 2024)
Salawati District, as one of the agricultural centers in Sorong Regency, has 82.43% of its population employed in the agricultural sector. Over time, the community faces various challenges threatening the food supply and agricultural sustainability. The success of soil and water conservation practices heavily relies on the participation and contribution of local communities. This research aims to identify adopted soil and water conservation practices, assess the level of knowledge regarding these practices, and evaluate their impact on sustainable food production. The research design combines qualitative and quantitative approaches. Results indicate that the local community's knowledge stands at 72.86%, with 82.86% implementing soil and water conservation practices in agricultural cultivation processes. The primary motivation for applying conservation practices is to enhance agricultural yields (70%), followed by environmental sustainability concerns (15.71%) and personal motivations (14.29%). Challenges faced include a lack of resources (34.29%), weather uncertainties (30%), insufficient knowledge about conservation practices (22.86%), and time constraints (12.86%). Information sources for implementing soil and water conservation practices include other farmers (51.43%), the internet or social media (37.14%), local agricultural experts (8.57%), and agricultural training (2.86%). Farmer groups serve as the primary support system for implementing soil and water conservation practices, with 100% of the local community having a more sustainable outlook on increasing local food production. Sustainable agricultural systems can be achieved by improving land quality, ultimately enhancing sustainable food production and achieving food security.